Khurshid Mahmud Kasuri, Neither a Hawk Nor a Dove: An Insider’s Account of Pakistan’s Foreign Relations - Muhammad Faisal (CISS Insight Journal, 2015)
Since 1947 Pakistani leaders and policy-makers have dealt with what can be called, “Pakistan’s India problem”. They have pursued hawkish policies and adopted dovish postures. Between these two extreme approaches, former Foreign Minister (FM), Khurshaid Kasuri, stands out as a ‘centrist’. He has penned a voluminous memoir-policy book on Pakistan’s foreign affairs from the vantage point of having remained the steward of Pakistan’s diplomacy during 2002-07. Mr. Kasuri, provides insights into Pakistan’s complex relations with India, Afghanistan and the United States, while surveying Islamabad’s ties with rest of the world and also commenting on domestic politics to contextualize the discussion. The main focus of the book, however, is on India-Pakistan relations and related developments during his tenure as foreign minister. Centrist Kasuri, who refuses accept the label of a hawk or a dove, says he learnt to embrace the middle path from his father who while being a practising Muslim was also a staunch Marxist. The experience of being brought up in an environment shaped by his father’s personality left a deep imprint on Kasuri.